Chest x-ray feature of venous air embolism in orthopedic surgery in prone position: A case report - Liu, Yuwu; Gao, Qun; Chen, Andi; Xiao, Jian; Shi, Ping (Frontiers in Surgery, 2023)
Background Venous air embolism (VAE) is a life-threatening event characterized as a series of clinical features of the disease caused by gas entering the venous circulation in the body. Case presentation A 72-year-old male patient with an ankle fracture after trauma was admitted, and complained of chest pain and dyspnea after the ankle fracture resection and internal fixation. His heart rate and blood pressure dropped, and the patient was diagnosed with VAE according to a chest x-ray and clinical features. Cardiopulmonary resuscitation was carried out and the patient's heartbeat recovered; his blood pressure rose to a normal level. The patient was still unconscious and sent to the intensive care unit for continued monitoring and treatment. Unfortunately, the patient discharged himself from the hospital and died 24 h later. Conclusion This case suggests that x-ray may be a potential method for the rapid diagnosis of VAE in a resource-limited setting.